Mineralogy, geochemistry and petrography of methane-derived authigenic carbonates from Enza River, Northern Apennines (Italy). (September 2015) - Viola, I.; Oppo, D.; Franchi, F.; Capozzi, R.; Dinelli, E.; Liverani, B.; Taviani, M.
Abstract: A remarkable exposure of carbonate pipe-like and slab concretions occurs along the Enza riverbanks on the Northern Apennines foothills (Italy). Based upon geochemical and field evidences, their genesis has been attributed to microbial-governed carbonate precipitation from hydrocarbon-enriched fluids. The pipe-like concretions are thus interpreted as former conduits (chimneys) marking sites of methane ascent onto the seafloor. The resulting Enza River chimney field is arranged in a palisade fashion, a rare example of such. Mineralogical and petrographic analyses of some chimneys and slabs document that the dominant cement is dolomite. Although the chimneys show a rather homogeneous texture, a clear zonation is observed in the relative distribution of major and minor elements in their internal and external parts. The occurrence of sulphide minerals in the stratigraphically upper samples indicates possible renewal of fluids leakage after a major erosive event. Highlights: Methane derived authigenic carbonates in the Northern Apennines (Italy). Geochemistry of carbonate chimneys and slabs and of the hosting marine sediments. Anaerobic methane oxidation and sulphate reduction promote carbonate precipitation. Dolomite cements indicate precipitation in sulphate-depleted pore waters. Secondary alteration of carbonates due fluid leakage after their formation.